Pulmonary artery perfusion versus no perfusion during cardiopulmonary bypass for open heart surgery in adults - Buggeskov, Katrine B (Cochrane Database Syst Rev, 2018)
BACKGROUND: Available evidence has been inconclusive on whether pulmonary artery perfusion during cardiopulmonary bypass (CPB) is associated with decreased or increased mortality, pulmonary events, and serious adverse events (SAEs) after open heart surgery. To our knowledge, no previous systematic reviews have included meta‐analyses of these interventions. OBJECTIVES: To assess the benefits and harms of single‐shot or continuous pulmonary artery perfusion with blood (oxygenated or deoxygenated) or a preservation solution compared with no perfusion during cardiopulmonary bypass (CPB) in terms of mortality, pulmonary events, serious adverse events (SAEs), and increased inflammatory markers for adult surgical patients. SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, Embase, Science Citation Index Expanded, and advanced Google for relevant studies. We handsearched retrieved study reports and scanned citations of included studies and relevant reviews to ensure that no relevant trials were missed. We searched for ongoing trials and unpublished trials in the World Health Organization International Clinical Trials Registry Platform (ICTRP) and at clinicaltrials.gov (4 July 2017). We contacted medicinal firms producing preservation solutions to retrieve additional studies conducted to examine relevant interventions. SELECTION CRITERIA: We included randomized controlled trials (RCTs) that compared pulmonary artery perfusion versus no perfusion during CPB in adult patients (≧ 18 years). DATA COLLECTION AND ANALYSIS: Two independent review authors extracted data, conducted fixed‐effect and random‐effects meta‐analyses, and calculated risk ratios (RRs) or odds ratios (ORs) for dichotomous outcomes. For continuous data, we have presented mean differences (MDs) and 95% confidence intervals (CIs) as estimates of the intervention effect. To minimize the risk of systematic error, we assessed risk of bias of included trials. To reduce the risk of random errors caused by sparse data and repetitive updating of cumulative meta‐analyses, we applied Trial Sequential Analyses (TSAs). We used GRADE principles to assess the quality of evidence. MAIN RESULTS: We included in this review four RCTs (210 participants) reporting relevant outcomes. Investigators randomly assigned participants to pulmonary artery perfusion with blood versus no perfusion during CPB. Only one trial included the pulmonary artery perfusion intervention with a preservation solution; therefore we did not perform meta‐analysis. Likewise, only one trial reported patient‐specific data for the outcome "pulmonary events"; therefore we have provided no results from meta‐analysis. Instead, review authors added two explorative secondary outcomes for this version of the review: the ratio of partial pressure of oxygen in arterial blood (PaO(2)) to fraction of inspired oxygen (FiO(2)); and intubation time. Last, review authors found no comparable data for the secondary outcome inflammatory markers. The effect of pulmonary artery perfusion on all‐cause mortality was uncertain (Peto OR 1.78, 95% CI 0.43 to 7.40; TSA adjusted CI 0.01 to 493; 4 studies, 210 participants; GRADE: very low quality). Sensitivity analysis of one trial with overall low risk of bias (except for blinding of personnel during the surgical procedure) yielded no evidence of a difference for mortality (Peto OR 1.65, 95% CI 0.27 to 10.15; 1 study, 60 participants). The TSA calculated required information size was not reached and the futility boundaries did not cross; thus this analysis cannot refute a 100% increase in mortality. The effect of pulmonary artery perfusion with blood on SAEs was likewise uncertain (RR 1.12, 95% CI 0.66 to 1.89; 3 studies, 180 participants; GRADE: very low quality). Data show an association between pulmonary artery perfusion with blood during CPB and a higher postoperative PaO(2)/FiO(2) ratio (MD 27.80, 95% CI 5.67 to 49.93; 3 studies, 119 participants; TSA adjusted CI 5.67 to 49.93; GRADE: very low quality), although TSA could not confirm or refute a 10% increase in the PaO(2)/FiO(2) ratio, as the required information size was not reached. AUTHORS' CONCLUSIONS: The effects of pulmonary artery perfusion with blood during cardiopulmonary bypass (CPB) are uncertain owing to the small numbers of participants included in meta‐analyses. Risks of death and serious adverse events may be higher with pulmonary artery perfusion with blood during CPB, and robust evidence for any beneficial effects is lacking. Future randomized controlled trials (RCTs) should provide long‐term follow‐up and patient stratification by preoperative lung function and other documented risk factors for mortality. One study that is awaiting classification (epub abstract with preliminary results) may change the results of this review when full study details have been published.